Modelling of zirconium alloy hydrogenation - Zaika, Yury V; Rodchenkova, Natalia I (Journal of physics. Conference series, 2016)
Zirconium alloys are the construction materials for critical elements in active zones of nuclear power reactors. During the operation of reactors such materials are subject to hydrogenation. Hydrogenation results in a decrease of alloy plasticity and cracking resistance. The formation of brittle hydrides at crack tips can result in severe embrittlement. One of the most important requirements for the reactor's active zone materials is low hydrogen absorptivity. The mathematical model of hydride layer formation and growth is developed. The problem is to determine the dynamics of the free boundary of phase interface and the distributions of hydrogen concentration in hydride and in solution. Iterative computational algorithm for solving the nonlinear boundary-value problem with the Stefan condition based on implicit difference schemes is developed.